2020
DOI: 10.1097/mpg.0000000000002633
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon‐like Peptide 2 Concentrations Vary in Zambian Children During Diarrhoea, in Malnutrition and Seasonally

Abstract: Objectives Glucagon-like peptide 2 (GLP-2) is a 33 amino acid peptide hormone released from enteroendocrine L-cells following nutrient ingestion. It has been shown to exert trophic effects on the gut. We set out to measure GLP-2 concentrations in blood in children with diarrhoea and malnutrition. Methods GLP-2 levels were measured in blood samples collected from 5 different groups of children (n = 324) at different time points: those with acute diarrhoea, during illness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…We have also shown that in children with diarrhoea, GLP‐2 levels are elevated in acute but not persistent diarrhoea. In malnutrition and enteropathy, GLP‐2 levels progressively declined as the children's growth became more stunted (Amadi et al., 2017 ; Besa et al., 2020 ). We set out to test the hypothesis that reduced circulating GLP‐2 levels in children with environmental enteropathy and stunting is attributable to small intestinal EEC loss or reduced function, assessed by immunostaining, transcriptomic and genomic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…We have also shown that in children with diarrhoea, GLP‐2 levels are elevated in acute but not persistent diarrhoea. In malnutrition and enteropathy, GLP‐2 levels progressively declined as the children's growth became more stunted (Amadi et al., 2017 ; Besa et al., 2020 ). We set out to test the hypothesis that reduced circulating GLP‐2 levels in children with environmental enteropathy and stunting is attributable to small intestinal EEC loss or reduced function, assessed by immunostaining, transcriptomic and genomic analysis.…”
Section: Introductionmentioning
confidence: 99%